Research, project, implementation. The case study of the former Riganti Tannery in Rome - Andrea Grimaldi; Valeria Sansoni (Agathón)
While the recovery of monumental buildings is now customary, less obvious is the recovery of the built non-monumental heritage as a result of a historization of events and economic and social activities occurred over time. The subject of this contribution is the experience of research and design carried out on the former Riganti Tannery, a building complex annexed to Villa Poniatowski and part of the real estate heritage of the National Etruscan Museum of Villa Giulia in Rome. Between conservation tout court and radical changes, this research proposes a third way: the addition of a new design ‘level’ as a device to link history with contemporaneity. The contribution also proposes an innovative strategy of collaboration between Institutions, in order to bring the project to the core of an effective process of cultural development.